Amorphous Cobalt Boride (Co 2 B) as a Highly Efficient Nonprecious Catalyst for Electrochemical Water Splitting: Oxygen and Hydrogen Evolution - Masa, Justus; Weide, Philipp; Peeters, Daniel; Schuhmann, Wolfgang (Advanced Energy Materials, 2016)
It is demonstrated that amorphous cobalt boride (Co2B) prepared by the chemical reduction of CoCl2 using NaBH4 is an exceptionally efficient electrocatalyst for the oxygen evolution reaction (OER) in alkaline electrolytes and is simultaneously active for catalyzing the hydrogen evolution reaction (HER). The catalyst achieves a current density of 10 mA cm−2 at 1.61 V on an inert support and at 1.59 V when impregnated with nitrogen-doped graphene. Stable performance is maintained at 10 mA cm−2 for at least 60 h. The optimized catalyst, Co2B annealed at 500 °C (Co2B-500) evolves oxygen more efficiently than RuO2 and IrO2, and its performance matches the best cobalt-based catalysts reported to date. Co2B is irreversibly oxidized at OER conditions to form a CoOOH surface layer. The active form of the catalyst is therefore represented as CoOOH/Co2B. EXAFS observations indicate that boron induces lattice strain in the crystal structure of the metal, which potentially diminishes the thermodynamic and kinetic barrier of the hydroxylation reaction, formation of the OOH* intermediate, a key limiting step in the OER.